2019
DOI: 10.1177/0972150919856993
|View full text |Cite
|
Sign up to set email alerts
|

Do Indian Companies Manage Earnings Before Share Repurchase?

Abstract: This article aims to detect the opportunistic EM before share buyback and its impact on the short-term and long-term abnormal return. The study also examines the relationship between EM and promoters’ holdings in the company. A sample of 117 companies over 1998–2013 is analyzed in the study. The quality of earnings is measured using discretionary accruals (DAs), and it is calculated by four different methods, that is, the Healy model (1985), DeAngelo model (1986), modified Jones model (1995) and performance-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…EPS improvements are a primary corporate driver of stock repurchases, according to Cao et al (2020), who found a positive correlation between earnings management strategies and stock repurchases in Vietnam. Jena et al (2019) found that promoter holdings and earnings quality are negatively correlated, and Indian companies engage in opportunistic earnings management before buybacks. According to Xu and Taylor (2017), firms use stock repurchases to control earnings.…”
Section: Introductionmentioning
confidence: 99%
“…EPS improvements are a primary corporate driver of stock repurchases, according to Cao et al (2020), who found a positive correlation between earnings management strategies and stock repurchases in Vietnam. Jena et al (2019) found that promoter holdings and earnings quality are negatively correlated, and Indian companies engage in opportunistic earnings management before buybacks. According to Xu and Taylor (2017), firms use stock repurchases to control earnings.…”
Section: Introductionmentioning
confidence: 99%